2014
DOI: 10.1016/j.conbuildmat.2013.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and mineralogical properties of natural hydraulic lime-metakaolin mortars in different curing conditions

Abstract: Grilo, J.; Santos Silva, A.; Faria, P.; Gameiro, A.; Veiga, R.; Velosa, A. Mechanical and mineralogical properties of natural hydraulic lime-metakaolin mortars in different curing conditions. Construction and Building Materials, v. 51, p. 287-294, 2014. January 2014 1 Tests were conducted at different curing ages, using compressive and flexural strength tests and thermogravimetric and X-ray diffraction techniques.NHL mortars cured at high humidity levels in natural and artificial environments present intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 23 publications
11
42
0
1
Order By: Relevance
“…However, mortars with MK show a general strength decrease over time for all curing conditions (except for M curing with 10% MK), suggesting instability of the hydrated compounds that are formed. This fact was discussed elsewhere based on mineralogical and chemical analysis [11] and has already been pointed out for different formulations, with air lime and MK [31] and hydraulic limes [16]. …”
Section: March 2014 19mentioning
confidence: 99%
See 1 more Smart Citation
“…However, mortars with MK show a general strength decrease over time for all curing conditions (except for M curing with 10% MK), suggesting instability of the hydrated compounds that are formed. This fact was discussed elsewhere based on mineralogical and chemical analysis [11] and has already been pointed out for different formulations, with air lime and MK [31] and hydraulic limes [16]. …”
Section: March 2014 19mentioning
confidence: 99%
“…Different curing conditions produce changes in characteristics due to the development of chemical reactions in time [16,18] and propitiate different developments in the setting and hardening reactions, which will influence the mortars strength, porosity and microstructure [11,19]. Actually, the onsite curing conditions are completely different from laboratory standardized conditions, so it is important to analyze the influence of this factor, by testing mortars with different curing conditions, either laboratorial or natural.…”
Section: March 2014mentioning
confidence: 99%
“…cement, sand, water and mineral or chemical additives. Various types of powders/fillers such as fly ash, silica fume, metakaolin, limestone, glass, ground granulated blast furnace slag, bentonite, rice husk ash, coconut shell ash have already been investigated by the researchers for the production of high performance cement composites [4][5][6][7][8][9][10][11][12]. The utilization of the nano/micro-sized fillers improves the mechanical performance due to the secondary hydration, heterogeneous nucleation and/or due to the filling effect of small particles C [13].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics and properties NHLs present when they are used with pozzolanic materials need thorough and in-depth investigation. Grilo et al (2014) found that the strength of mortars increased when metakaolin was added to prepare NHL-based mortars, but a decrease of strength with ageing was observed with metakaolin incorporation. A high humidity condition was advantageous for hydration and pozzolanic reaction.…”
mentioning
confidence: 91%